1474 Practices in the railway industry for assessments, intervention and management of psychosocial issues in south africa. (24th April 2018) - Bester, M
Abstract : Introduction: There are a number of psychosocial issues prevalent in the rail industry that influence workers' health and wellbeing. Managing psychosocial risks is a legal imperative that oblige employers to establish processes in accordance with national legislation to match task and environments to the physical and psychological capabilities of people to safeguard their health and wellbeing. Globalisation, higher workload and more pressure, increased job insecurity as well as poor work life balance contribute to these psychosocial issues. Methods: An analysis of questionnaire responses from Occupational health practitioners working in the railway industry, to describe types of assessments, various interventions and management of workers with psychosocial issues were conducted. Consideration were given to reason for consultation, follow-ups, and referrals to secondary psychological interventions where indicated. Result: The results revealed that we are lacking information that could provide insight into the magnitude of the problem that can influence policies and practices in the workplace. Effective solutions is needed for the prevention of psychosocial risks as these offer good returns in improved efficiency and productivity, better health, reduced absenteeism and lower medical costs. Discussion: It is widely acknowledged that work and life related stress is very common and has a high cost in terms of workers health, absenteeism and lower performance in the workplace. The development of effective guidelines, processes and policies is important to assist occupational health practitioners in assisting workers to get expert advice and referral at point of service to deal with psychosocial issues. Conclusion: A comprehensive approach by practitioners and new patterns of prevention is necessary to face current psychosocial issues in the workplace. It proved repeatedly that effective solutions should exist for the prevention of psychosocial issues as this offer good return in terms of reduced absenteeism, better health, improved work efficiency and productivity.